Compensation Management In Pekanbaru City Government Environment In 2021 (Study On Giving Additional Employee Income - Raja Malinda Jeliantika; Hasim As'ari; Dadang Mashur (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
This research is motivated by the problems that occur within the Pekanbaru City government in providing additional employee income (TPP). The problem that occurs is there is a cut in the provision of TPP in 2021 to employees. In this case, the provision of TPP goes through a long process and it is not given how much each employee will receive but through several processes first. There are several aspects that will be used as an assessment in determining the amount of TPP. The purpose of this study is to determine the compensation management system, especially in providing additional employee income (TPP) in the Pekanbaru City government environment and the authors want to analyze the constraints that exist in compensation management in providing additional employee income (TPP). This study uses the theory of Dessler (2014) which describes five stages in providing compensation, namely surveys, job evaluation, classifying work, giving prices for each level and improving payment levels. This study uses qualitative research with interview and documentation techniques. The results of the study show that compensation management, especially in the provision of additional employee income (TPP), is still not running smoothly. The reason for the cut in the provision of TPP to employees is budget constraints and in 2021, existing funds are diverted to health, because in 2021 there will be an increase in cases of Covid-19. In carrying out compensation management, of course there are inhibiting factors such as the lack of employee participation in carrying out the compensation management process and budget constraints.